Indicadores Culturales Como Complemento Decisivo De La Sostenibilidad Integral Sistema De Indicadores Culturales Como Aporte A La Determinacion De La Sostenibilidad Integral Urbana De Riobamba, Provincia De Chimborazo - Catalina Margarita Verdugo Bernal; Carlos Arturo Jara Santillán; Carla Sofía Arguello Guadalupe; Christiam Paul Aguirre Merino; Paulina Beatriz Díaz Moyota; Otto Fernando Balseca Sampedro; Miguel Ángel Duque Vaca (European Scientific Journal, ESJ, 2016)
In view of the lack of a system of cultural indicators in Riobamba County, the present study develops a series of steps that lead to the obtaining of a list of indicators relevant for the cultural management of the five urban parishes of the county. The data generated by this research will contribute to a general study that intends to rank the city among the 150 most sustainable cities in the world, this will be seen in a future publication as other areas of urban sustainability will be included to determine the integral sustainability of the territory. Initially the research analyzes several models of indicators proposed by organizations and experts understood in the cultural subject at global, regional and local level. We proceed to discriminate these proposed models by looking for their proximity to the local reality. In addition, further information was collected that contributed to generate new cultural indicators of the city through citizen participation. With the help of local authorities, the information collected together was analyzed to determine the indicators that directly affect the level of cultural sustainability of the five parishes in the city. Finally all results are reflected in the publication of a newsletter with statistical summaries where the situation of some cultural aspects of the riobambeña population is reflected in order to make feasible suggestions for improvement and to reinforce the local culture.